Autogenous boné graft in the posterior region of the mandible: Clinical case report (Research, Society and Development, 2025)
Tooth loss is a significant challenge in dentistry, as it can lead to resorption of the alveolar ridge, resulting in both aesthetic and functional deficiencies. The installation of osseointegrated implants emerges as an effective solution to restore masticatory function and minimize these consequences. However, for this procedure to be viable, it is essential that the bone volume in the area to be implanted is adequate. When there is insufficient bone, the use of bone grafts becomes necessary. Autogenous grafts are considered the gold standard in bone regeneration due to their osteogenic, osteoconductive, and osteoinductive properties, which favor more effective tissue repair. This study aims to report a clinical case of block autogenous bone grafting in the posterior region of the mandible, with the goal of promoting bone height and thickness gain, preparing the area for future rehabilitation with osseointegrated implants. The clinical case involves a 53-year-old female patient who presented with partial edentulism in the left mandible, accompanied by complaints of chewing difficulties and aesthetic dissatisfaction. After a detailed clinical evaluation and a computed tomography scan, it was found that the bone thickness in the posterior region of the mandible was insufficient for implant placement. Therefore, it was decided to perform a block autogenous bone graft, harvested from the ramus region of the right side. The surgical procedure was successfully performed, and the patient received the necessary postoperative care. After 30 days, a new tomography revealed good positioning of the graft and signs of bone neoformation, indicating that the procedure was effective. It is concluded that block autogenous bone grafting proved to be a promising technique for the reconstruction of the alveolar ridge in atrophic mandibles, providing adequate bone volume gain for subsequent rehabilitation with osseointegrated implants.